Digital marketing strategy on travel tourism businesses in marketing 4.0 era - Dewi, Ni Putu Rekha Chandra (International research journal of management, IT and social sciences, 2020)
An online-based transportation system has been created thanks to the industrial revolution 4.0, indirectly this system will slowly begin to shift transportation services such as travel that still uses conventional marketing systems. Social media is a media platform that focuses on the existence of users who facilitate them in their activities and collaborations. So in this case, the media can be seen as a virtual medium that strengthens between users as well as a social bond. According to social media is the media used by consumers to share text, images, sound, and video information both with others and companies and vice versa. With these unique characteristics, social media can be used as an effective business promotion tool. Wonderfull Bali is a company engaged in the field of travel tourism. In addition to travel tours, Wonderfull Bali also caters for events, car and motorbike rentals, spas & massages, shops, yoga, beauty, and skincare. The travel agent industry is no longer able to rely on walk-in service for ticket reservations and choosing travel packages, everything has changed with digital.